Strength training and geriatric morbidities: a review - Antonini, Tiago Cippolat (2012)
The muscular force of the human body is directly related with your development, where the largest amount of muscular force happens between the 20 and 30 initial years of life, happening in the twenty following years a drastic reduction of the muscular cells. This reduction of muscular cells reaches a negative index considerably loud in the 60 years of life and it continues happening in the most advanced ages. This article treats of a revision that aimed at to problematize the training of force for senior. A literature survey focused on resistance training for older people was made from the following sources. A literature review ofarticles indexed in Medline and following the methodology suggested for the implementation of this article, only one book was chosen as a reference base. In the Medline indexing the keywords used for the selection of the articles were: "strength training elderly" for the period 1979 to September 2009. A total of 3597 articles were identified with the theme, and 313 reviews. Given the large number of publications, this study focused its analysis on reviews involving strength training with geriatric major morbidities and later with reviews on strength training and biology of aging.